Lepidoptera of South Ossetia (Northern Transcaucasia). Part I. Introduction and Superfamily Pyraloidea Latreille, 1809 - Aleksandr N. Streltzov; Petr Ya. Ustjuzhanin; Roman V. Yakovlev (Acta Biologica Sibirica, 2022)
In the first part of the publication, we present the faunal list of Pyraloidea of South Ossetia, including 111 species of 64 genera, belonging to two families. For the first time, 96 species are reported for South Ossetia. Scoparia manifestella (Herrich-Schäffer, 1848) and Scoparia perplexella (Zeller, 1839) are found in the Caucasus for the first time, and the new species Scoparia sinevi Streltzov, 2022 is currently indicated as an endemic of South Ossetia.